Serum Ferritin in Thalassemia Intermedia - Shah, Ravi (Indian J Hematol Blood Transfus, 2013)
Serum ferritin is a useful monitoring tool for iron overload in thalassemia major. In resource poor settings access to modalities for assessment of iron overload are limited. This study was undertaken to assess the efficiency and usefulness of serum ferritin level in thalassemia intermedia (TI) patients. This was a cross sectional observational study. Seventy seven TI patients attending the pediatric hematology clinic were included. Fasting blood sample was taken from each patient in iron free vials for iron studies. Serum ferritin was estimated by immunometric enzyme immunoassay using Orgentec GmbH kits. Mean age of patients evaluated was 10.9 ± 5.03 (3–26) years. The mean age at diagnosis was 4.21 ± 2.3 (0.8–11) years. Mean serum ferritin was 486.54 ± 640.0 ng/ml (15–4,554). Thirty two (41.5 %) patients had a ferritin value of ≥500 ng/ml. Nine patients had a serum ferritin of ≥1,000 ng/ml. Three of the subjects with a ferritin >1,000 ng/ml had never received a blood transfusion (BT) and in the other six, the number of BTs ranged from 1 to 8. Serum ferritin did not correlate with age, total number of BTs splenectomy status or BT in last one year (p > 0.05). In 41.5 % of TI patients, serum ferritin was ≥500 ng/ml. Age, BT and splenectomized status did not affect ferritin level. We postulate interplay of other biological factors like HFE gene mutation, ferroportin, etc. to contribute to ferritin level and hence iron load in TI patients. Ferritin can possibly be used as screening and monitoring tool for iron load in TI patients when other modalities to assess iron overload are not easily available.